2015
DOI: 10.1039/c4sc03277b
|View full text |Cite
|
Sign up to set email alerts
|

A fully recyclable heterogenized Cu catalyst for the general carbene transfer reaction in batch and flow

Abstract: Carbene transfer reactions can be performed in batch and flow with a highly active, chemically stable heterogenized tris(triazolyl)methyl copper(i) catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 55 publications
1
33
0
2
Order By: Relevance
“…We reasoned that, if the complex was formed from a cationic copper species rather than with CuCl, the chances of leaching would diminish. Consequently, solid‐supported TTM was treated with [Cu(MeCN) 4 ]PF 6 and the resulting cationic complex 28 was benchmarked with the ethyl diazoacetate insertion onto ethanol, in the framework of a collaboration with the group of Díaz‐Requejo and Pérez from the University of Huelva . The system was incredibly robust, allowing for a flow process that spanned 48 h working at flow rates as high as 500 μL min −1 .…”
Section: Immobilized Ligands and Metal‐based Catalysts For Work In Flowmentioning
confidence: 99%
“…We reasoned that, if the complex was formed from a cationic copper species rather than with CuCl, the chances of leaching would diminish. Consequently, solid‐supported TTM was treated with [Cu(MeCN) 4 ]PF 6 and the resulting cationic complex 28 was benchmarked with the ethyl diazoacetate insertion onto ethanol, in the framework of a collaboration with the group of Díaz‐Requejo and Pérez from the University of Huelva . The system was incredibly robust, allowing for a flow process that spanned 48 h working at flow rates as high as 500 μL min −1 .…”
Section: Immobilized Ligands and Metal‐based Catalysts For Work In Flowmentioning
confidence: 99%
“…Very recently, Díaz-Requejo, Pérez and Pericàs et al 71 reported on the preparation of a fully recyclable heterogenized cationic copper(I) complex 34 and its catalytic performance in carbene transfer reactions 72 The heterogenized system 34 (5.2 mol%) efficiently catalysed a diverse variety of carbene transfer reactions, under neat conditions or in DCM as solvent at rt, by using inexpensive ethyl diazoacetate (40) as the carbene source (Scheme 19). 71 Insertion reactions of the carbene unit into C−H bonds of cyclohexane (35) and tetrahydrofuran (36), the O−H bond of ethanol (37) and the N−H bond of aniline (14a), as well as addition reactions to benzene (38; Büchner reaction) and 1-phenyl-1-propyne (39; cyclopropenation) were all successfully performed giving rise to an array of products (41−46) in very high yields (82 99% yield).…”
Section: Scheme 17 Cuaac Reactions Mediated By Ps-supported 9h·cuclmentioning
confidence: 99%
“…71 Insertion reactions of the carbene unit into C−H bonds of cyclohexane (35) and tetrahydrofuran (36), the O−H bond of ethanol (37) and the N−H bond of aniline (14a), as well as addition reactions to benzene (38; Büchner reaction) and 1-phenyl-1-propyne (39; cyclopropenation) were all successfully performed giving rise to an array of products (41−46) in very high yields (82 99% yield). After each carbene transfer reaction, the catalyst was readily separated by simple filtration and reused for next cycle.…”
Section: Scheme 17 Cuaac Reactions Mediated By Ps-supported 9h·cuclmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the polystyrene-linked tris(triazolyl)methanecopper (I) cationic catalyst 162 was reported for the general carbene transfer reaction in batch and flow reactions [103]. It was prepared by reaction between the polystyrene-supported tris(triazolyl) methyl complex 161 and [Cu (MeCN)4][PF6] in dichloromethane at room temperature (Scheme 62).…”
Section: Miscellaneous Examplesmentioning
confidence: 99%